Energi terbarukan dan Pemanfaatan Tanaman Kaliandra Untuk Eko edu wisata - Nasython, Kun (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
Calliandra (Calliandra calothyrsus) is a fast-growing, multi-purpose shrub known for its woody stems, dense canopy, and deep-rooting system that reaches 1.5 to 2 meters. This species can be harvested within one year and offers multiple ecological and economic benefits. With a nitrogen-fixing root system, C. calothyrsus improves soil fertility and resilience, making it suitable for degraded lands. The plant resists fire, pests, and diseases and produces high-calorific value energy wood (~4000 Kcal) with minimal ash content. As a Multiple Purpose Tree Species (MPTS), it serves as fuelwood, livestock fodder, soil conditioner, and a nectar source for honeybee farming. Based on its versatility, this study explores the potential of cultivating Calliandra through an integrated farming approach and eco-edu tourism development. The objective is to assess how Calliandra farming can provide renewable energy while promoting environmental education, local community empowerment, and regional economic growth. The research employs a descriptive qualitative method, combining field observations, interviews with farmers, and literature analysis. The findings indicate that Calliandra cultivation supports environmental restoration and opens opportunities for ecotourism and agroforestry-based livelihoods. The study implies that Calliandra farming can become a strategic trigger for sustainable rural development and local revenue enhancement.